Selective activation of SIGMAR1 in anterior cingulate cortex glutamatergic neurons facilitates comorbid pain in depression in male mice - Xianlei Wang; Shulin Wu; Junsheng Zuo; Keying Li; Yutong Chen; Zhijie Fan; Zhou Wu; Jun-Xia Yang; Weiyi Song; Jun-Li Cao; Mengqiao Cui (Communications Biology)
Abstract Depression and comorbid pain are frequently encountered clinically, and the comorbidity complicates the overall medical management. However, the mechanism whereby depression triggers development of pain needs to be further elucidated. Here, by using the chronic restraint stress (CRS) mouse model of depression and comorbid pain, we showed that CRS hyperactivated the glutamatergic neurons in the anterior cingulate cortex (ACC), as well as increasing the dendrite complexity and number. Chemogenetic activation of these neurons can induce depression and pain, while chemogenetic blockade can reverse such depression-induced pain. Moreover, we utilized translating ribosome affinity purification (TRAP) in combination with c-Fos-tTA strategy and pharmacological approaches and identified SIGMAR1 as a potential therapeutic molecular target. These results revealed a previously unknown neural mechanism for depression and pain comorbidity and provided new mechanistic insights into the antidepressive and analgesic effects of the disease.